P.119 Emergency Department Use in Children with Cerebral Palsy: A Data Linkage Study. (November 2021) - Fortin, O; Ng, P; Dorais, M; Koclas, L; Pigeon, N; Shevell, M; Oskoui, M
Abstract : Background: Improved understanding of factors predictive of emergency department (ED) visits in children with cerebral palsy (CP) can help optimize healthcare use. We sought to identify the pattern of ED consultations in these children. Methods: Data from the Registre de paralysie cérébrale du Québec and provincial administrative databases were linked. The CP cohort was comprised of children born between 1999 and 2002. Data pertaining to ED presentations between 1999 and 2012 were obtained. Relative risks were calculated to identify factors associated with increased ED visits. Peers without CP were selected from administrative databases and matched in a 20:1 ratio. Chi-square tests and Student's T-tests were used to compare the two cohorts. Results: 301 children with CP and 6040 peer controls were selected. Ninety-two percent (92%) of the CP cohort had at least one ED visit, compared to 74% amongst controls. Children with CP had an increased risk of high ED use compared to peers (RR 1.40 95% CI 1.30-1.52). Factors predictive of high ED use were comorbid epilepsy, severe motor impairment and low socioeconomic status. Conclusions: Children with CP have a higher need for urgent health assessments than their peers, resulting in increased use of ED services. System factors and barriers should be investigated.